1980
DOI: 10.1111/j.1471-4159.1980.tb11181.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of N‐Acetylmannosamine into Rat Brain Subcellular Gangliosides: Effect of Pentylenetetrazol‐Induced Convulsions on Brain Gangliosides1

Abstract: The labeling pattern of the major individual gangliosides from the microsomal and synaptosomal fractions of rat brain was determined following intracerebral injection of the radioactive sialic acid precursor, N‐acetylmannosamine. Microsomal gangliosides initially had a higher specific radioactivity than synaptosomal gangliosides, with both fractions reaching similar specific radioactivities 18 h after precursor injection. In both subcellular fractions, the polysialogangliosides GT1b and GQ1b were initially mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Since analytical methodologies are subject to variation in different laboratories, comparisons carried out in the same laboratory are perhaps more instructive than comparisons between laboratories. Analogous to this study, Avrova et al (1973) also found similarities in ganglioside patterns of unfractionated SPM and MIC and more recently Yohe et al (1980) observed closely similar patterns between microsomes and whole synaptosomes of rat brain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Since analytical methodologies are subject to variation in different laboratories, comparisons carried out in the same laboratory are perhaps more instructive than comparisons between laboratories. Analogous to this study, Avrova et al (1973) also found similarities in ganglioside patterns of unfractionated SPM and MIC and more recently Yohe et al (1980) observed closely similar patterns between microsomes and whole synaptosomes of rat brain.…”
Section: Discussionsupporting
confidence: 88%
“…Generally similar patterns were previously reported for microsomal gangliosides of rat brain (Avrova et al, 1973;Yohe et al, 1980) and rabbit brain (Tettamanti et al, 1973), although those studies reported somewhat lower values for G M~ and higher values for GD~,. The SPM ganglioside pattern obtained in this study showed lower proportions of GD2/GTla, and GDlb and more G M~ than that reported previously for unfractionated SPM (Avrova et al, 1973).…”
Section: Discussionsupporting
confidence: 88%
“…the plasma membrane. Support for this assumption comes from studies of ganglioside biosynthesis, where no precursor-product relationship is found between the simple and complex gangliosides (Caputto et al, 1974; Maccioni et al, 1977;Yohe et al, 1980;Miller-Podraza and Fishman, 1983). In other words, most gangliosides exist in the plasma membrane as end-products, rather than intracellularly as precursors.…”
Section: Ganglioside Gdmentioning
confidence: 99%
“…1999). In addition, pentylenetetrazol‐induced seizures affect the contents of the subcellular gangliosides (Yohe et al . 1980).…”
mentioning
confidence: 99%
“…Alternatively, it was proposed that gangliosides containing sialic acid, in which the contents in the brain were fivefold greater than that in other tissues (Iwamori and Nagai 1981), have a supporting effect on the regulation of calcium and nitric oxide in signaling in the plasma membrane (Rahmann 1995;Pyo et al 1999). In addition, pentylenetetrazol-induced seizures affect the contents of the subcellular gangliosides (Yohe et al 1980). However, how these molecules contribute to neural plasticity remains essentially unknown.…”
mentioning
confidence: 99%